ChemInform Abstract: Ba3Pt4Al4 — Structure, Properties, and Theoretical and NMR Spectroscopic Investigations of a Complex Platinide Featuring Heterocubane [Pt4Al4] Units. Issue 3 (29th December 2015) - Stegemann, Frank; Benndorf, Christopher; Bartsch, Timo; Touzani, Rachid St.; Bartsch, Manfred; Zacharias, Helmut; Fokwa, Boniface P. T.; Eckert, Hellmut; Janka, Oliver
Abstract: The title compound is prepared from the elements (Nb tube, 1073 K, 7 d) and characterized by powder XRD, XPS, 27 Al MAS NMR spectroscopy, magnetic measurements, and DFT band structure calculations.